Evaluation of the inferior alveolar nerve with 3 tesla turbo spin echo magnetic resonance imaging - BORAHAN, MEHMET OĞUZ; ÇİMŞİT, NURİ ÇAGATAY (My University, 2022)
Objectives: The purpose of this study is to evaluate the inferior alveolar nerve’s position and nerve plexus within the mandibular canal (MC) with turbo spin echo (TSE) sequences of magnetic resonance imaging (MRI). Methods: The IAN position was evaluated retrospectively in 220 patients as right and left mandibles (n=440). IAN was classified according to topographical features and branches. MRI images were evaluated as the sequences of T1-weighted, T2- weighted and Proton Density TSE images with standard scanning protocols. Additionally, location of the nerve plexus was recorded as anterior, premolar, molar and retromolar regions. Results: Patient age was in the range of 7-81 years and the mean age was 37.23 ±16.38. Most common type was Type I (75.2%) which identifies a single major branch of IAN, followed by Type II (21.8%) that identifies inferiorly located and extended branching IAN, and Type III (3%) which represents IAN divides posteriorly into two major branches. Also, it was found that molar region nerve plexus (66.2%) was significantly higher than other regions. Conclusions: MRI is a non-invasive soft tissue imaging method and is an alternative promising modality regarding in the evaluation of IAN. Preoperative MRI examination may help surgical planning of mandible molar region to avoid complications.

Giriş: Bu çalışmanın amacı inferior alveolar sinirin konumunu ve mandibular kanalın içerisindeki sinir demetinin morfolojik sınıflamasını turbo spin eko manyetik rezonans görüntüleme (TSE MRG) ile değerlendirmektir. Materyal ve Metod: Inferior alveolar sinirin konumu, 220 hastaya ait manyetik rezonans görüntülerinde sağ ve sol olarak (n=440) retrospektif olarak sagittal, koronal ve aksiyal kesitlerde değerlendirilmiştir. Inferior alveolar sinir topografik özelliklerine ve dallanmalarına göre sınıflandırılmıştır. Manyetik rezonans görüntüleri T1 ağırlıklı, T2 ağırlıklı, Proton Density olarak kaydedilmiştir. Sinir pleksusunun konumu anterior, premolar, molar, retromolar olarak kaydedilmiştir. Bulgular: Yaş aralığı 7-81 ve yaş ortalaması 37.23±16.38 olmuştur. En sık görülen inferior alveolar sinir, tek bir sinir dalını ifade eden Tip I (75.2%) olmuştur. İkinci en sık görülen Tip II (%21.8) olup, mandibulanın inferiorundan geçen, uzamış sinir dallanmaları izlenen tipi olmuştur. Posteriorda iki ana dala ayrılan inferior alveolar sinir tipi Tip III olup, görülme sıklığı %3 olarak saptanmıştır. En sık görülen sinir demeti bölgesi molar bölge (%66.2) olarak bulunmuştur. Sonuç: MRG, invaziv olmayan bir yumuşak doku görüntüleme yöntemi olup inferior alveolar siniri görüntülemede alternatif bir yardımcı yöntem olabilir. Preopertatif olarak MRG, mandibula molar bölgenin cerrahi planlamasında kullanılabilir.
Inferior alveolar sinirin 3 tesla turbo spin eko manyetik rezonans görüntüleme yöntemiyle değerlendirilmesi
Keywords: inferior alveolar nerve; mandible; mandibular canal; magnetic resonance imaging; turbo spin echo; inferior alveolar sinir; mandibula; mandibular kanal; manyetik rezonans görüntüleme; turbo spin eko